Impact of finerenone on chronic kidney disease progression in Chinese patients with type 2 diabetes: a FIGARO-DKD subgroup analysis - Li, Ping; Zheng, Hongguang; Ma, Jianhua; Lu, Weiping; Li, Ling; Liu, Fang; Su, Qing; Li, Yuxiu; Fang, Yi; Mo, Zhaohui; Xiong, Fei; Yin, Aiping; et al. (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes (T2D) is a considerable and growing burden in the Chinese population, and affected adults are at high risk of developing chronic kidney disease (CKD). This subgroup analysis of the FIGARO-DKD trial explored the cardiovascular and kidney benefits of finerenone in Chinese patients with CKD and T2D on optimized renin–angiotensin system blockade.MethodsPatients with urine albumin-to-creatinine ratio (UACR) ≥30–<300 mg/g and estimated glomerular filtration rate (eGFR) ≥25–≤90 mL/min/1.73 m2, or UACR ≥300–≤5000 mg/g and eGFR ≥60 mL/min/1.73 m2, were randomized to finerenone or placebo. The primary cardiovascular composite outcome was time to cardiovascular death, non-fatal myocardial infarction, non-fatal stroke, or hospitalization for heart failure. The secondary kidney composite outcome was time to kidney failure, sustained eGFR decline ≥40% from baseline, or kidney-related death.ResultsA total of 325 Chinese patients were included. Finerenone resulted in a numerical decrease in the risk of the cardiovascular composite outcome (hazard ratio 0.91; 95% confidence interval 0.50–1.67) and a significantly reduced risk of the key secondary kidney outcome (hazard ratio 0.48; 95% confidence interval 0.29–0.79; p = 0.0029). The incidence of investigator-reported hyperkalemia was high across both treatment arms. Nevertheless, the incidence of hyperkalemia leading to hospitalization and treatment discontinuation was low across treatment arms.ConclusionsFinerenone significantly reduced the composite kidney outcome, showed a trend to reduce cardiovascular outcomes, and demonstrated an acceptable safety profile in Chinese patients.